The Natural History of Scaphoid Fracture Malunion: A Scoping Review - Seltser, Anna; Suh, Nina; MacDermid, Joy C.; Grewal, Ruby (Journal of Wrist Surgery, 2020)
Background A scaphoid malunion occurs when a scaphoid fracture heals in a nonanatomic position or when the fracture is fixed without correction of the sagittal angular deformity. Although altered carpal mechanics and early osteoarthritis have been suggested as natural sequelae, the natural history and clinical outcomes are debatable.Purposes The purpose of this study is to review and summarize the available literature regarding clinical, functional, and radiographic outcomes of patients with scaphoid malunion.Methods A systematic search of the MEDLINE/PubMed, EMBASE, Cochrane Library, and Web of Science was performed to identify published studies concerning the clinical and radiological results of scaphoid malunion following either acute scaphoid fracture or surgically treated nonunions.Results Five publications with a total of 83 malunions were included in the final synthesis. The diagnosis of malunion was based on computed tomography by calculating the lateral intrascaphoid angle (threshold of 35 or 45 degrees) or height/length ratio (threshold of 0.6). Self-reported and clinical evaluation techniques varied between the studies and direct comparison was not possible between the different outcome measures. Most patients demonstrated arthritic changes; however, correlation with pain and functional results was not always present.Conclusions This scoping review confirmed that patients with malunited scaphoids seem to have higher likelihood of post traumatic arthritis. However, clinical implications remain uncertain and better methods for assessing and defining scaphoid deformity are required.
Keywords: scaphoid fracture; malunion; traumatic arthritis